2018
DOI: 10.1088/1674-4926/39/9/094001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single walled carbon nanotubes on series resistance of Rose Bengal and Methyl Red dye-based organic photovoltaic device

Abstract: The influence of single walled carbon nanotube (SWCNT) on the series resistance (Rs) of Rose Bengal (RB) and Methyl Red (MR) dye-based organic diodes has been studied. It has been revealed from experimental results that SWCNT has a significant effect on Rs. The values of Rs are measured from current–voltage (I–V) characteristics and also by utilizing the Cheung method. Obtained values from the Cheung method have been verified using H(I)–I plots for all dye-based devices. The extracted values using these two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Experimentally observed current-voltage (I-V) characteristics of these organic devices are compatible with thermionic emission theory. The current through a metal-organic semiconductor interface due to thermionic emission theory can be expressed as [9][10][11][12][13]…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally observed current-voltage (I-V) characteristics of these organic devices are compatible with thermionic emission theory. The current through a metal-organic semiconductor interface due to thermionic emission theory can be expressed as [9][10][11][12][13]…”
Section: Resultsmentioning
confidence: 99%
“…The current through a metal-organic semiconductor interface due to thermionic emission can be expressed as (Sze and Kwok, 2007;Chakraborty et al, 2018;Shah et al, 2010a;Yakuphanoglu, 2010;Aydın et al, 2006):…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the device efficiency is maximum for 200 nm device layer thickness and efficiency reduces consequently with increasing thickness of active region.For minimum thickness of active layer the blocking impact of charges is minimum and conducting charges travel a minimum conducting path which inherently reduces the trapping problem [14][15][16][17]. Due to the lower effect of trapping energy series resistance effect for abovementioned layer thickness is small enough which enhance the probability of maximum conduction and therefore maximum efficiency is obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Open Access/Spectrum 2019/Special Issue www.mahendrapublications.com of conduction, Indium Tin Oxide (ITO) film is chosen as front electrode and Al metal as back electrode for easy charge collection [13][14]. Donor-acceptor blend of active composite material permits absorption of light and exciton generation.…”
Section: Chakraborty Et Almentioning
confidence: 99%